Characterization of the electrophysiological substrate in patients with Barlow's disease. (28th October 2021) - Vergara, Pasquale; Scarfò, Iside; Esposito, Antonio; Colantoni, Caterina; Palmisano, Anna; Altizio, Savino; Falasconi, Giulio; Pannone, Luigi; Lapenna, Elisabetta; Gulletta, Simone; Alfieri, Ottavio; Castiglioni, Alessandro; et al.
Abstract: Background: Myxomatous mitral valve prolapse (MVP) and mitral‐annular disjunction (Barlow disease) are at‐risk for ventricular arrhythmias (VA). Fibrosis involving the papillary muscles and/or the infero‐basal left ventricular (LV) wall was reported at autopsy in sudden cardiac death (SCD) patients with MVP. Objectives: We investigated the electrophysiological substrate subtending VA in MVP patients with Barlow disease phenotype. Methods: Twenty‐three patients with VA were enrolled, including five with syncope and four with a history of SCD. Unipolar (Uni < 8.3 mV) and bipolar (Bi < 1.5 mV) low‐voltage areas were analyzed with electro‐anatomical mapping (EAM), and VA inducibility was evaluated with programmed ventricular stimulation (PES). Electrophysiological parameters were correlated with VA patterns, electrocardiogram (ECG) inferior negative T wave (nTW), and late gadolinium enhancement (LGE) assessed by cardiac magnetic resonance. Results: Premature ventricular complex (PVC) burden was 12 061.9 ± 12 994.6/24 h with a papillary‐muscle type (PM‐PVC) in 18 patients (68%). Twelve‐lead ECG showed nTW in 12 patients (43.5%). A large Uni less than 8.3 mV area (62.4 ± 45.5 cm 2 ) was detected in the basal infero‐lateral LV region in 12 (73%) patients, and in the papillary muscles (2.2 ± 2.9 cm 2 ) in 5 (30%) of 15 patients undergoing EAM. A concomitant Bi less than 1.5 mV area (5.0 ± 1.0 cm 2 ) was identified in two patients. A history of SCD, and the presence of nTW, and LGE were associated with a greater Uni less than 8.3 mV extension: (32.8 ± 3.1 cm 2 vs. 9.2 ± 8.7 cm 2 ), nTW (20.1 ± 11.0 vs. 4.1 ± 3.8 cm 2 ), and LGE (19.2 ± 11.7 cm 2 vs. 1.0 ± 2.0 cm 2, p = .013), respectively. All patients with PM‐PVC had a Uni less than 8.3 mV area. Sustained VA (ventricular tachycardia 2 and VF 2) were induced by PES only in four patients (one with resuscitated SCD). Conclusions: Low unipolar low voltage areas can be identified with EAM in the basal inferolateral LV region and in the papillary muscles as a potential electrophysiological substrate for VA and SCD in patients with MVP and Barlow disease phenotype.